2015
DOI: 10.1007/s10750-015-2487-7
|View full text |Cite
|
Sign up to set email alerts
|

The meroplankton communities from the coastal Ross Sea: a latitudinal study

Abstract: The study of meroplankton communities in the coastal Ross Sea has been difficult due to the logistical challenges associated with sampling in remote areas and with the hurdle of larval identification. As a result, it has not been possible to estimate the latitudinal changes in reproductive strategies of marine invertebrates and to investigate Thorson's rule-that planktotrophy is less favoured than lecithotrophy and brooding at high latitudes-along the southernmost coastline on Earth. As part of the Latitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Molecular signatures of deep sea and continental shelf refugia have been suggested for species with pelagic development including the shrimp Nematocarcinus lanceopes (Raupach et al 2010), the sea urchin Sterechinus neumayeri (Díaz et al 2018) and two cryptic species within the crinoid Promachocrinus kerguelensis (Hemery et al 2012), as well as those with direct development including the sea spider Nymphon australe (Soler‐Membrives et al 2017), and the octopod Pareledone turqueti (Strugnell et al 2012, 2017). Despite the apparent evolutionary success of a direct developing strategy to survive glacial cycles, pelagic larvae are found in Antarctic waters from a wide range of phyla, including Arthropoda, Bryozoa, Cnidaria, Echinodermata, Mollusca, Nematoda and Porifera (Shreeve and Peck 1995, Stanwell‐Smith et al 1999, Sewell 2005, Freire et al 2006, Bowden et al 2009, Sewell and Jury 2011, Ameneiro et al 2012, Gallego et al 2015). The molecular evidence of glacial survival and modern observations of pelagic and non‐pelagic development in extant benthic fauna reflect that both strategies clearly contributed unique ways of assisting fauna to persist through glacial periods.…”
Section: Pathways To Glacial Refugia Through Larval Dispersalmentioning
confidence: 99%
See 3 more Smart Citations
“…Molecular signatures of deep sea and continental shelf refugia have been suggested for species with pelagic development including the shrimp Nematocarcinus lanceopes (Raupach et al 2010), the sea urchin Sterechinus neumayeri (Díaz et al 2018) and two cryptic species within the crinoid Promachocrinus kerguelensis (Hemery et al 2012), as well as those with direct development including the sea spider Nymphon australe (Soler‐Membrives et al 2017), and the octopod Pareledone turqueti (Strugnell et al 2012, 2017). Despite the apparent evolutionary success of a direct developing strategy to survive glacial cycles, pelagic larvae are found in Antarctic waters from a wide range of phyla, including Arthropoda, Bryozoa, Cnidaria, Echinodermata, Mollusca, Nematoda and Porifera (Shreeve and Peck 1995, Stanwell‐Smith et al 1999, Sewell 2005, Freire et al 2006, Bowden et al 2009, Sewell and Jury 2011, Ameneiro et al 2012, Gallego et al 2015). The molecular evidence of glacial survival and modern observations of pelagic and non‐pelagic development in extant benthic fauna reflect that both strategies clearly contributed unique ways of assisting fauna to persist through glacial periods.…”
Section: Pathways To Glacial Refugia Through Larval Dispersalmentioning
confidence: 99%
“…In an effort to examine whether Thorson's rule (i.e. high latitudes do not favour planktotrophy in marine invertebrates, Mileikovsky 1971) applies to the Western Ross Sea, Gallego et al (2015) performed plankton surveys to measure the larval diversity characterised by planktotrophy and lecithotrophy over multiple summer seasons. This study revealed that at least 70% of larval diversity sampled (Molecular Operational Taxonomical Units; mOTUs) during summer seasons were comprised of planktotrophic mOTUs (Gallego et al 2015).…”
Section: Pelagic Larval Survival Throughout Glacial Cyclesmentioning
confidence: 99%
See 2 more Smart Citations
“…In large part due to extensive DNA barcoding efforts, such as done through the Census of Marine Life (McIntyre, 2010) and a growing richness of reference libraries (i.e., Barcode of Life Data Systems, BOLD 1 ), it is becoming increasingly feasible to use barcoding instead of, or in addition to, morphology to describe biodiversity in marine ecosystems. Yet to date, there are only a few studies focusing on meroplankton at the species level, and even fewer from the high latitudes (i.e., Stanwell-Smith et al, 1999;Sewell, 2005;Fetzer and Arntz, 2008;Bowden et al, 2009;Heimeier et al, 2010;Sewell and Jury, 2011;Gallego et al, 2015;Silberberger et al, 2016;Brandner et al, 2017). The Pacific Arctic region is no exception; although both benthic (Grebmeier et al, 2006;Bluhm et al, 2009;Grebmeier, 2012;Iken et al, 2018) and pelagic (Hopcroft et al, 2010;Eisner et al, 2013;Ershova et al, 2015a;Pinchuk and Eisner, 2017) summer communities of the Chukchi Sea, particularly on the United States side, have been studied extensively and described in great detail during the last decades (Day et al, 2013;Sigler et al, 2017), meroplankton has been largely overlooked, with FIGURE 1 | Major oceanographic features of the Chukchi Sea (modified from Stabeno et al, 2018) and locations of macrobenthic hotspots as defined by Grebmeier et al (2015b).…”
Section: Introductionmentioning
confidence: 99%